Zero-Trust Architecture in Distributed Financial Ecosystems - Purella, Satyanarayana (International Journal of Computing and Engineering, 2025)
Contemporary financial institutions face unprecedented challenges in securing distributed digital ecosystems characterized by cloud-native implementations, microservices architectures, and extensive third-party integrations. Traditional perimeter-based security models prove inadequate against sophisticated cyber threats that exploit the interconnected nature of modern banking infrastructure. Zero Trust Architecture emerges as a transformative security paradigm that operates on the fundamental principle of "never trust, always verify," treating all users, devices, and network communications as potentially compromised entities regardless of location or authentication history. This comprehensive framework addresses the complex security requirements of distributed financial environments through explicit verification protocols, least privilege access controls, and continuous threat monitoring capabilities. The implementation encompasses service mesh technologies that provide cryptographic verification of service identities, identity-aware proxies that enable contextual access control, and dynamic authorization systems powered by machine learning algorithms. Financial institutions benefit from enhanced security posture through mutual Transport Layer Security protocols, automated certificate lifecycle management, and sophisticated traffic segmentation strategies that align with regulatory compliance requirements. The framework addresses critical challenges in cross-border transaction processing, digital wallet integration, and fintech aggregator security while maintaining operational efficiency and user experience quality. Zero Trust principles enable financial organizations to demonstrate regulatory compliance across multiple jurisdictions while significantly reducing security incident frequencies and associated remediation costs.